Blue Ocean Strategy untuk Meningkatkan Daya Saing Ekspor Kerajinan Kerang - Desak Made Wulandewi; Luh Putu Mahyuni (Universitas Batanghari Jambi, 2023)
This study aims to explore how the Blue Ocean Strategy can be applied to the shellfish industry and other industries to increase export volume. The type of research used is qualitative research. Data was collected through interviews. From the research results, the competitive strategy used by Egy Shell at this time are focus and branding strategy. Egy Shell is becoming more focused on customer service and making the company more widely known. On the other hand, the company faces a tight competitive strategy because competitors are also targeting the same market. It is necessary to improve the current competitive strategy and formulate a new strategy using the Blue Ocean Strategy. From the formulation of the competitive strategy, new strategies that can be applied include: improving Product Quality by training the skills of craftsmen, Marketing by utilizing social media. In addition, it is necessary to create adequate facilities, create a company website so that it is easy to get company information, maximize the timeliness of product completion and carry out product innovations regularly.